Growth, phenology and yield of drought tolerant rainfed rice cultivars to staggered transplanting dates under changing climatic scenarios of central terai, Nepal - Karki, D. B.; Amgain, L. P. (Journal of the Institute of Agriculture and Animal Science, 2018)
A field experiment entitled “growth, phenology and yield of drought tolerant rainfed rice cultivars to staggered transplanting dates under changing climatic scenarios of central terai, Nepal” was conducted at farmer’s field in Dhobadi VDC, Nawalparasi (27°40'N, 84°05'E and 235 masl) during June to November, 2012. The experimental soil was determined silt loam with slightly acidic reaction (pH-5.67). About 1960.40 mm of total rainfall was recorded at the experimental site during crop growing period which was 17.56% lower than average of the past 15 years (2378 mm). The experiment consisted sixteen treatment combinations arranged in split-plot design i.e. four transplanting dates in main-plot and four cultivars in sub-plot with three replications. The statistical result on grain yield revealed significant differences among dates of transplanting, however, varietal differences were found to be non-significant. The maximum (2.46 t ha-1) and minimum (0.30 t ha-1) grain yield were recorded for first transplanting date (July 15) and last transplanting date (August 14), respectively. Grain yield, number of grains panicle-1, filled grains panicle-1 and test weight recorded under July 15, July 25 and August 4 transplanted condition were statistically at par but was significantly superior over August 14 transplanting. The reduction in grain yield due to successive delay of 10 days from July 15 upto August 4 was to the extent of 12.6 and 28.6 percent, respectively. GDD received by rice cultivars was found significantly higher (2830 °C) for July 15 transplanted rice at maturity stage, whereas, August 14 transplanted rice received significantly lower GDD (2689 °C) for maintaining maturity stage. Cultivar Sukkha Dhan-2 was found relatively more stable in using heat for all transplanting dates (86.31%) followed by Sukkha Dhan-3 (86.66 %), Sukkha Dhan-1 (88.31%) and Radha-4 (88.37 %). Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 157-164